Paciente masculino de 4 años diagnosticado con neumonía bacteriana. - Ayala García, Tulio Andrés (2021)
The current clinical case study based on a 4-year-old male patient diagnosed with bacterial pneumonia where the general objective is to use respiratory therapy techniques, according to the Pan American Health Organization, pneumonia is considered a respiratory infection, which affects Mainly to the alveolar sacs, the alveolar sacs can cause different causes, such as the filling of liquids and other secretions, which can cause various complications in the system. In the respiratory tract, the most common occurrence is respiratory failure and O2 absorption. The population with the highest risk of bacterial pneumonia in the community includes neonates, pediatrics and the elderly, among them, because the immune system is not fully developed or deteriorated by age or foundation, they are the most vulnerable to pathologies, such as HIV, AIDS, cancer, etc. Pneumonia is very often preceded by a few days with symptoms of upper respiratory infection, especially rhinitis and cough. The present study was based on a patient with an unstable clinical picture, in which there is hyperthermia, frequent cough, accompanied by vomiting, respiratory distress, muscle weakness, through physical examination the patient can hear abnormal lung sounds (stridor, wheezing) nasal flapping. The causative agent was streptococcus pneumoniae, which was controlled with an antibiotic treatment, through respiratory distress that could be evidenced was linked to the pathology which was counteracted with oxygen therapy treatment and other respiratory therapy techniques.